SILIA: software implementation of a multi-channel, multi-frequency lock-in amplifier for spectroscopy and imaging applications. (20th September 2021) - Nadgir, Amrut; Thurston, Richard; Larsen, Kirk A; Shivaram, Niranjan; Brister, Matthew M; Slaughter, Daniel S
Abstract: We describe a software implementation of a multi-channel, multi-frequency Lock-in Amplifier (SILIA) to extract modulated signals from noisy data distributed over multiple channels of arbitrary number and size. This software implementation emulates the functionality of a multi-channel, multi-frequency lock-in amplifier in a post-processing step following data acquisition. Unlike most traditional lock-in amplifiers, SILIA can work with any number of input channels and is especially useful to analyze data distributed over many channels. We demonstrate the versatility and performance for extracting weak signals in spectroscopy and fluorescence microscopy. We also discuss more general applications and exhibit a method to automatically estimate error from a lock-in result.